Spatial working memory is critical for gesture processing: Evidence from gestures with varying semantic links to speech - Özer, Demet; Özyürek, Aslı; Göksun, Tilbe (Psychonomic bulletin & review, 2025)
Gestures express redundant or complementary information to speech they accompany by depicting visual and spatial features of referents. In doing so, they recruit both spatial and verbal cognitive resources that underpin the processing of visual semantic information and its integration with speech. The relation between spatial and verbal skills and gesture comprehension, where gestures may serve different roles in relation to speech is yet to be explored. This study examined the role of spatial and verbal skills in processing gestures that expressed redundant or complementary information to speech during the comprehension of spatial relations between objects. Turkish-speaking adults ( N =74) watched videos describing the spatial location of objects that involved perspective-taking (left-right) or not (on-under) with speech and gesture. Gestures either conveyed redundant information to speech (e.g., saying and gesturing “left” ) or complemented the accompanying demonstrative in speech (e.g., saying “ here, ” gesturing “left” ). We also measured participants’ spatial (the Corsi block span and the mental rotation tasks) and verbal skills (the digit span task). Our results revealed nuanced interactions between these skills and spatial language comprehension, depending on the modality in which the information was expressed. One insight emerged prominently. Spatial skills, particularly spatial working memory capacity, were related to enhanced comprehension of visual semantic information conveyed through gestures especially when this information was not present in the accompanying speech. This study highlights the critical role of spatial working memory in gesture processing and underscores the importance of examining the interplay among cognitive and contextual factors to understand the complex dynamics of multimodal language.